Early-onset dementia among privately-insured adults with and without congenital heart defects in the United States, 2015–2017. (1st July 2022) - Downing, Karrie F.; Oster, Matthew E.; Olivari, Benjamin S.; Farr, Sherry L.
Highlights: Adults with CHD were 2× as likely as those without CHD to have early-onset dementia. Early-onset dementia was associated with CHD among males but not females. Early-onset dementia was associated with CHD in both age groups (45–54 & 55–64 yrs). Results were similar comparing those with non-severe CHD to no CHD.